Toxicological Investigation of a Case Series Involving the Synthetic Cathinone α-Pyrrolidinohexiophenone (α-PHP) and Identification of Phase I and II Metabolites in Human Urine. Issue 2 (3rd August 2022) - Grapp, Marcel; Kaufmann, Christoph; Schwelm, Hannes M; Neukamm, Merja A
Abstract: α-Pyrrolidinohexiophenone (α-PHP) is a derivative of the class of α-pyrrolidinophenones, a subgroup of synthetic cathinones. These substances are the second most abused drugs of new psychoactive substances. Here, we report the toxicological investigation of a series of 29 authentic forensic and clinical cases with analytically confirmed intake of α-PHP including two cases of drug testing in newborns using meconium. The age range of subjects where serum samples were available was 23–51 years (median 39.5), and 90% were male. Serum α-PHP concentrations, determined by a validated LC–MS-MS method, showed a high variability ranging from 1 to 83 ng/mL (mean, 40 ng/mL; median, 36 ng/mL). Comprehensive toxicological analysis revealed co-consumption of other psychotropic drugs in almost all cases with frequent occurrence of opiates (60%), benzodiazepines (35%), cannabinoids (30%), and cocaine (20%). Hence, forensic and clinical symptoms like aggressive behavior, sweating, delayed physical response, and impaired balance could not be explained by the abuse of α-PHP alone but rather by poly-intoxications. Liquid chromatography-quadrupole time-of-flight mass spectrometry and gas chromatography-mass spectrometry were used to investigate the metabolism of α-PHP in vivo using authentic human urine samples. Altogether, 11 phase I metabolites and 5 phase II glucuronides could be identified by this approach. Apart from the parent drug, most abundant findings in urine were the metabolites dihydroxy-pyrrolidinyl-α-PHP and dihydro-α-PHP and, to a lesser extent, 2ʹ-oxo-dihydro-α-PHP and 2ʹ-oxo-α-PHP. Monitoring of these metabolites along with the parent drug in forensic and clinical toxicology could unambiguously prove the abuse of the novel designer drug α-PHP.